DC-DRF: Adaptive Multi-Resource Sharing at Public Cloud Scale - Kash, Ian; O'Shea, Greg; Volos, Stavros (2018 ACM Symposium on Cloud Computing, 2018)
Public cloud datacenters implement a distributed computing environment built for economy at scale, with hundreds of thousands of compute and storage servers and a large population of predominantly small customers often densely packed to a compute server. Several recent contributions have investigated how equitable sharing and differentiated services can be achieved in this multi-resource environment, using the Extended Dominant Resource Fairness (EDRF) algorithm. However, we find that EDRF requires prohibitive execution time when employed at datacenter scale due to its iterative nature and polynomial time complexity; its closed-form expression does not alter its asymptotic complexity. In response, we propose Deadline-Constrained DRF, or DC-DRF, an adaptive approximation of EDRF designed to support centralized multi-resource allocation at datacenter scale in bounded time. The approximation introduces error which can be reduced using a high-performance implementation, drawing on parallelization techniques from the field of High-Performance Computing and vector arithmetic instructions available in modern server processors. We evaluate DC-DRF at scales that exceed those previously reported by several orders of magnitude, calculating resource allocations for one million predominantly small tenants and one hundred thousand resources, in seconds. Our parallel implementation preserves the properties of EDRF up to a small error, and empirical results show that the error introduced by approximation is insignificant for practical purposes.